PENGGGUNAAN MODEL MIND MAP DALAM PENINGKATAN HASIL BELAJAR IPS TENTANG PERKEMBANGAN TEKNOLOGI SISWA KELAS IV SD NEGERI 2 JATISARI KECAMATAN KEBUMEN KABUPATEN KEBUMEN TAHUN AJARAN 2014/2015 - AGUSTIN, WINDA FITRIANI (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: Application of Model Mind Map in Improving Learning Outcomes IPS on Technology Development IV Elementary School Grade 2 Jatisari District of Kebumen Kebumen Academic Year 2014/2015. This study aims to (1) describe the use of mind mapping models in improving learning outcomes IPS about technological developments fourth grade students of SD Negeri 2 Jatisari academic year 2014/2015. (2) improve learning outcomes IPS about technological developments fourth grade students of SD Negeri 2 Jatisari academic year 2014/2015. (3) describe the obstacles and solutions use mind mapping models in improving learning outcomes IPS about technological developments fourth grade students of SD Negeri 2 Jatisari academic year 2014/2015. This study is a collaborative action research conducted in three cycles, each cycle includes the stages of planning, implementation, observation and reflection. Based on the results of hypothesis testing can be concluded that the use of the model mind map according to the procedure correctly it can improve learning outcomes IPS about technological developments fourth grade students of SD Negeri 2 Kebumen Kebumen Jatisari District of the academic year 2014/2015. In the pre-action completeness percentage reaches 25% of new students, having carried out the action on the first cycle completeness percentage of students increased to 93.85%, in the second cycle and third cycle increased to 96.42%.Keywords: model of Mind Map, student learning outcomes, IPS, technological developments